The Potential of Science Education for Development of Responsible Citizenship in Ukraine - Denys Svyrydenko; Frol Revin (Studia Warmińskie)
Our research focuses on how sociocultural processes can foster responsible citizenship in Ukraine through scientific literacy within an overarching philosophical narrative. In particular, the authors aim to outline various dilemmas, beginning with the ambiguities that science education faces when confronting notions of good citizenship within differing sociocultural contexts. Hence, we focus on the ethical and moral aspects of citizenship within a science education agenda that is not reducible to the learning of scientific facts. We show that it is an essential instrument for developing critical rationality, moral judgment and civic involvement. This agenda is centered around the development of scientific literacy, motivating students to engage in their own auto-didactic pursuit of scientific inquiry. The authors maintain that this sense of curiosity and critical engagement is bound to translate into an ability to make sense of difficult ethical and social Ukrainian terrain as well as positively influence approaches to pedagogical education. We further examine Ukrainian science education curriculum in the context of the broader national and global challenges of attaining scientific literacy as a foundational pillar of any future learning and teaching. More specifically, the authors propose a policy rooted in evidence-based inquiry as a centerpiece of all progressive education to allow students to develop the tools they need to become better informed, active citizens able to bring about positive societal shifts. The findings of our study relate to the call for educational reform in Ukraine through the modernization of both its physical and pedagogical infrastructure. The case is made for creating a strong foundation of scientifically-minded attitudes amongst the well-informed citizenry, which will lead to a generation able to consider and address complex ethical and social issues. The research interprets its results in terms of a broader philosophical and educational discourse with a view as to how military conflicts can affect the producing an informed population able to direct its concerted efforts towards the development of sustainable, equitable progress that serves both the individual and society at large.